DEVELOP EARLY LITERACY SKILLS THROUGH COOPERATIVE LEARNING MODELS, MONTESSORI GAME METHODS AND SANDPAPER LETTERS MEDIA - Alda Laida; Dessy Dwitalia Sari (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2023)
This research was motivated by the low results of children's language development in the aspect of early literacy in recognizing and imitating (writing by mentioning) letters that are still not developed. The purpose ofthis study is teacher activity, child activity, and child development results in showing children's activities in recognizing and imitating (writing by mentioning) letters. This research approach uses a qualitative approach, the type of research is Classroom Action Research (PTK) which is carried out in 2 cycles. This researchwasconducted at Suka Maju Kindergarten, Lunjuk HST Village for the 2021/2022 school year in group A, which amounted to 12 children consisting of 4 boys and 8 girls. Datacollection techniques are carried out by observation, interviews, performances, and evaluation through LKPD. The results showed that teacher activity obtained very good categories, children's activities obtained very active categories, the results of the development of aspec early literacy aspects obtained categories developed as expected (BSH) and developed very well (BSB). The conclusion of this study is the use of cooperative learning models, Montessori game methods and sandpaper letters media in developing aspects of early literacy (recognizing and imitating) in group A children of Suka Maju Kindergarten Lunjuk HST Village.